Penyuluhan dan Pendampingan Pembuatan Teh Bunga Telang dan Sereh Wangi Untuk Menurunkan Kadar Gula Darah Di Desa Bandar Dawung Tawangmangu - Rifkarosita; Deva Amelia Andriani; Fani Widya Astri; Risa Amalia; Ravita Febi Astuti; Rohot Damianus Boru; Kusza Adelia; Epi Sekar Wangi; Irfan Bagus Setiawan; Pani (Jurnal Igakerta, 2024)
Community Service Lecture (CSL) is a community service program that is part of the higher education curriculum in Indonesia. The purpose of this program is to contribute to the community in Bandar Dawung village, Tawangmangu district, Central Java. One of the contributions given is the assistance program for making telang flower tea (Clitoria ternatea L.) and making jelly candy from citronella leaves (Cymbopogon citratus) is efficacious in lowering blood sugar levels. The main problem faced is the high prevalence of diabetes mellitus. Diabetes mellitus is a metabolic disease characterized by hyperglycemia, due to the body's relative and absolute insulin deficiency. The method used is divided into three stages, namely pre-activity, activity process, and evaluation. The results of this mentoring activity show that the level of public understanding of the benefits and processing of telang flowers and citronella leaves is 80%.